Desain Alat Filtrasi Sederhana Sistem Upflow, Variasi Bahan Filtrasi, dan Pengaruhnya Terhadap Penurunan Logam Besi dan Mangan - Rosdiana Rosdiana; Fatusman Muhammad Baguz; Al Amin Siharis; Wa Ndibale; Moch Assiddieq; Ilham Ilham; Bernadetha Susianti; Dwiprayogo Wibowo (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2022)
Water cleanliness plays an important role as a parameter in observing the quality of water that is suitable for consumption for every human life. This is certainly reflected in the health of a healthier life, but so far it is still low in the water quality that is suitable for community use. This study presents a simple technology to design water filtration using an up-flow system (bottom to up) and finds the effectiveness of the filtration media in reducing the content of iron (Fe) and manganese (Mn) metals in groundwater. Water samples were taken from Bukit Fadiah Asri Housing, Kendari City, and tested using three variations of media composition consisting of fiber, gravel, activated charcoal, black sand, and silica which flowed from bottom to top by gravity. Based on these results indicate that type B media material consisting of gravel, palm fiber, black sand, activated charcoal, silica, and palm fiber with a media thickness of 10 cm has a very good level of effectiveness which can reduce the metal content of Fe by 75% and Mn by 66%. This simple and inexpensive filtration media can be applied to the community to neutralize groundwater turbidity and reduce Fe and Mn metal content because it is used as an adsorption medium for heavy metals in water.